Reports, Songs, Press Conference
Report on the brave Iraqi soldiers' achieving victory, calling for Jihad; replays of womens' roll in the war, the artists' supporting the leadership, people supporting the leadership in the streets; Bedouin song, Sahhaf holding press conference with the media.